2011
DOI: 10.1074/jbc.m111.261545
|View full text |Cite
|
Sign up to set email alerts
|

CD133 Protein N-Glycosylation Processing Contributes to Cell Surface Recognition of the Primitive Cell Marker AC133 Epitope

Abstract: Background: Cell surface recognition of the AC133 epitope on CD133 marks many stem cell and cancer stem cell types. Results: A large scale RNA interference screen identifies genes involved in N-glycosylation that regulate cell surface AC133 recognition. Conclusion: CD133 N-glycosylation and its processing contribute to cell surface AC133 recognition. Significance: Glycobiological differences between primitive and differentiated cells may be responsible for regulating cell surface AC133.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
66
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 43 publications
(51 reference statements)
6
66
0
Order By: Relevance
“…We hypothesized that this is due to differential folding of CD133 on the surface of CSCs, which may be influenced by glycosylation that affects accessibility of the AC133 epitope (27). A recent report confirmed that N-glycosylation of CD133 determines the recognition of the AC133 epitope (28). We therefore conclude that the level of CD133 mRNA or protein is not a reliable marker for the presence and enumeration of CSCs.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…We hypothesized that this is due to differential folding of CD133 on the surface of CSCs, which may be influenced by glycosylation that affects accessibility of the AC133 epitope (27). A recent report confirmed that N-glycosylation of CD133 determines the recognition of the AC133 epitope (28). We therefore conclude that the level of CD133 mRNA or protein is not a reliable marker for the presence and enumeration of CSCs.…”
Section: Discussionmentioning
confidence: 44%
“…Previously, we found that the use of CD133 as a CSC marker depends on the availability of the AC133 epitope and is not determined by CD133 mRNA or protein expression, which remain unchanged during in vitro and in vivo differentiation of colon CSCs (27). Recently, it was confirmed that N-glycosylation of CD133 affects the cell surface recognition of AC133 (28). Altogether, this suggests that the prognostic value of CD133 in CRC is not due to an enumeration of CSCs.…”
Section: Introductionmentioning
confidence: 54%
“…Among the candidate genes PPEF1, PTPN7, PPP4C and PPP2R5E were previously shown to be important regulators of CD133 level emphasising the validity of our screen. 31 Moreover, several genes are reported to be relevant for stem cells, such as PPP4C identified in a previous RNAi screen for stem cell self-renewal factors, 21 DUSP5 described as an antidifferentiation regulator in embryonic stem cells 19 and PPEF1 identified as a marker for CD133 þ GSCs. 7 The selected candidate genes were validated in a secondary screen in three patient-derived GSC lines, but at variable level, which is most likely because of the molecular heterogeneity of tumour-derived patient samples.…”
Section: Discussionmentioning
confidence: 99%
“…The nature of CD133's epitope is a main factor that influenced the antibody binding (14). Both micromilieu and drug treatment could affect CD133 stability and its transport to the cell surface (15,16). We speculate that the different prognostic value may be due to different stem cell characteristics in subtypes of breast cancer.…”
Section: Discussionmentioning
confidence: 99%